2021
DOI: 10.3389/fpls.2021.685136
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Regulatory Mechanism of Color Diversity in Camellia japonica Petals by Integrative Transcriptome and Metabolome Analysis

Abstract: Camellia japonica petals are colorful, rich in anthocyanins, and possess important ornamental, edible, and medicinal value. However, the regulatory mechanism of anthocyanin accumulation in C. japonica is still unclear. In this study, an integrative analysis of the metabolome and transcriptome was conducted in five C. japonica cultivars with different petal colors. Overall, a total of 187 flavonoids were identified (including 25 anthocyanins), and 11 anthocyanins were markedly differentially accumulated among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 71 publications
4
45
0
Order By: Relevance
“… Jiang et al (2020) and Wang F. et al (2021) observed anthocyanins, such as cyanidin-3- O -glucoside and cyanidin-3,5- O -diglucoside (cyanin), from purple Salvia miltiorrhiza and purple Ficus carica Linn., respectively. Fu et al (2021) found that cyanidin-3- O -(6′′- O -malonyl)glucoside was the main contributor to the color of Camellia japonica . The results of these studies were similar to those of this study, and these DAAs may be the main reason for the difference in flower color between LS and JS.…”
Section: Discussionmentioning
confidence: 99%
“… Jiang et al (2020) and Wang F. et al (2021) observed anthocyanins, such as cyanidin-3- O -glucoside and cyanidin-3,5- O -diglucoside (cyanin), from purple Salvia miltiorrhiza and purple Ficus carica Linn., respectively. Fu et al (2021) found that cyanidin-3- O -(6′′- O -malonyl)glucoside was the main contributor to the color of Camellia japonica . The results of these studies were similar to those of this study, and these DAAs may be the main reason for the difference in flower color between LS and JS.…”
Section: Discussionmentioning
confidence: 99%
“…FvTCP9 dramatically promotes the genes involved in fruit color and aroma metabolism in strawberry fruits ( Wei et al, 2016 ). GATA promoted crucial genes of Ehrlich pathway to enhance 2-PE production in Saccharomyces cerevisiae ( Chen et al, 2017 ) and regulate anthocyanin accumulation in Camellia japonica petals ( Fu et al, 2021 ). The 14 TFs herein were also highly related to the genes in the biosynthesis of Phe and BPs.…”
Section: Discussionmentioning
confidence: 99%
“…bZIP, TCP, GATA, and so on (Wei et al, 2016;Chen et al, 2017;Jian et al, 2019;Gao et al, 2020;Fu et al, 2021). The important plant pigment anthocyanidins can be classified mainly into two groups, namely, flavonoids and phenolics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most plants except radish, carrot, and potato, anthocyanin biosynthesis and accumulation are induced by light [ 1 ]. The synthesis of anthocyanins is regulated by a variety of transcription factors, such as R2R3MYB [ 14 ], basic helix-loop-helix (bHLH) [ 15 ], WD40 protein [ 16 , 17 ], and WRKY [ 18 ]. Especially, MBW (MYB-bHLH-WDR) [ 19 ] protein complex play an important role in the flavonoid synthesis pathway.…”
Section: Introductionmentioning
confidence: 99%